Frequently Ill Child Syndrome - M. G. Romantsov; I. Yu. Melnikova; I. V. Sarvilina (Антибиотики и Химиотерапия)
The efficacy of cycloferon use in the treatment of frequently ill children (FIC) was estimated by the dynamics of the blood plasma proteomic profile. A group of FIC at the age of 4 to 10 years were observed. Cycloferon was administered according to the standard schemes. The results were analysed by the computer programme complex, including the anamnesis, clinical symptoms, infection index, findings of the electrophoretic and mass-spectrometric analyses of the blood plasma before and after the drug use. The intensity indices of the Rho and Ras proteins, the signal pathways, in the blood proteomic profile proved to be sensitive and specific parameters for estimating the regimens of the therapy and prophylaxis of respiratory tract infection in FIC. The epidemiologic efficacy of cycloferon, as an agent of nonspecific immunoprophylaxis for FIC during seasonal prevalence of respiratory tract infection and influenza cases was shown.